2019
DOI: 10.1038/s41598-019-51490-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Roughness on the Contact Line and Splashing Dynamics of Impacting Droplets

Abstract: Whether a droplet splashes upon impact onto a solid is known to depend not only on the fluid properties and its speed, but also on the substrate characteristics. Past research has shown that splashing is heavily influenced by the substrate roughness. Indeed, in this manuscript, we demonstrate that splashing is ruled by the surface roughness, the splashing ratio, and the dynamic contact angle. Experiments consist of water and ethanol droplets impacting onto solid substrates with varying degrees of roughness. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 55 publications
(71 reference statements)
1
46
1
Order By: Relevance
“…The values of the grit sizes for SC sandpapers are usually characterized by the European standard FEPA (Federation of European Producers of Abrasives), which is identical to the ISO (International Organization for Standardization) standard, while those for AO sandpapers are indicated through its colour, see table 1. The measurement of the substrate roughness through the grit size ε differs from that used by Range & Feuillebois (1998), Xu et al (2007), Tang et al (2017) and Hao (2017), who employed R a , see figure 2(a), or by Latka et al (2012), Quetzeri-Santiago et al (2019a and Roisman et al (2015), who made use of other parameters such as R pk or the root mean square roughness, R rms .…”
Section: Experimental Set-up and Phenomenologymentioning
confidence: 99%
See 2 more Smart Citations
“…The values of the grit sizes for SC sandpapers are usually characterized by the European standard FEPA (Federation of European Producers of Abrasives), which is identical to the ISO (International Organization for Standardization) standard, while those for AO sandpapers are indicated through its colour, see table 1. The measurement of the substrate roughness through the grit size ε differs from that used by Range & Feuillebois (1998), Xu et al (2007), Tang et al (2017) and Hao (2017), who employed R a , see figure 2(a), or by Latka et al (2012), Quetzeri-Santiago et al (2019a and Roisman et al (2015), who made use of other parameters such as R pk or the root mean square roughness, R rms .…”
Section: Experimental Set-up and Phenomenologymentioning
confidence: 99%
“…The experimental values of We, and Oh explored, as well as the values of the macroscopic static contact angle θ, are provided in table 1, where it is also shown that the grit size varies between ε ∼ 0.3 and ε ∼ 68 μm which results, using (2.1), in values of the mean roughness varying between R a ∼ 0.30 and R a ∼ 10.1 μm. Let us point out here that, since ε ∼ 0.014 μm for the case of smooth glass slides (Hao 2017;Quetzeri-Santiago et al 2019a), in the following, the value ∼ 10 −5 will be used to characterize the experiments corresponding to millimetric water or ethanol drops falling over smooth substrates. As was already pointed out in the introduction, no distinction will be made between prompt and…”
Section: Experimental Set-up and Phenomenologymentioning
confidence: 99%
See 1 more Smart Citation
“…with γ, surface tension, and m, the mass of the pool. The influence of roughness on the spreading and contact angle at equilibrium has been considered by several researchers 15,16 , who have shown that an increase in roughness leads to an increase in the maximum contact angle and a decrease in the final area. The results obtained and shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the values of contact angle observed for the films based on CSL AA and CSL GA with and without 10% LOADED nanofibers have been measured (Figure 12). The presence of the nanofiber network produces a slight decrease in contact angle, probably due to a change in surface roughness [54]. All the samples are characterized by contact angles lower than 70°, indicating good wetting properties.…”
Section: Preparation and Characterization Of Cs Filmsmentioning
confidence: 96%